Biogenic Synthesis of Silver Nanoparticles Using Terminalia chebula Retz. Leaf Extract and Evaluation of Biological Activities - Giri, Ramesh; Sharma, Khaga (Journal of Nepal Chemical Society, 2022)
Nanoparticles have been used in various fields of science and technology ranging from material science to biotechnology. The formation of nanoparticles has been confirmed through UV-visible spectroscopy (at 420 nm) by the change of color representing surface plasmon resonance. The synthesis of silver nanoparticles by a biogenic method is a novel approach due to its cost-effective, eco-friendly, and large-scale production possibilities. In the present study, silver nanoparticles (TC-AgNPs) were successfully synthesized using Terminalia chebula Retz. (T. chebula) leaf extract. Characterization of green synthesized silver nanoparticles was performed using UV-visible spectroscopy, Fourier transforms infrared (FTIR) spectroscopy, and X-ray diffraction (XRD). The formation of nanoparticles has been confirmed through UV-visible spectroscopy (at 420 nm) by the change of color representing surface plasmon resonance. The crystalline face-centred cubic property of the biosynthesized silver nanoparticles was established using XRD analysis. The XRD data gave the average particle size of 6.1 nm.  The functional groups such as -OH, C=O, =NH were found responsible for reducing silver ions and helping to stabilize nanoparticles which were analyzed using FTIR spectroscopy. As the silver nanoparticles possess diverse applications, TC-AgNPs were investigated for antioxidant, antibacterial, and cytotoxic activity. The results showed TC-AgNPs showed potential antioxidant (IC50=312.8 ± 2.28 µg/mL) and antibacterial activities against four pathogenic bacteria like Staphylococcus aureus, Acinetobacter baumannii, Salmonella typhi, and Escherichia coli. Also, the silver nanoparticles exhibited moderate cytotoxicity (LC50= 477.53 ± 0.684 µg/mL) against brine shrimps nauplii in a dose-dependent manner.